Liberalism, Pluralism and the Sphere Division in Harold Laski. Issue 170 (1st March 2022) - Gerson, Gal
Abstract: While aligned with John Neville Figgis' pluralism and Marxist socialism, Harold Laski endorsed liberal and democratic values. However, he synthesised several elements from older liberal theories in a way that diluted the division to which these theories had adhered, namely that between the private and the political spheres. The resulting combination preserves privacy's status as the realm where individuals are free to pursue their separate ends, but enables essentially private activities based in voluntary social spaces to infuse the space of politics. From this emerged a vision of liberal democracy, in which freedom plays out in multiple private spaces that do not require an autonomous civic arena to complement them. The combination was reached within the contexts of mid-century thinking about the welfare state and a broader project of reformulating democracy by reducing its equation with representation.